Pemetaan Dan Penentuan Jalur Evakuasi Di Desa Balahu Kecamatan Tibawa Kabupaten Gorontalo - Citron S. Payu; Dewa Gede Eka Setiawan; I Made Hermanto (Jurnal Masyarakat Mengabdi Nusantara, 2024)
Gorontalo Regency is one of the areas prone to annual flooding. One of the villages in Tibawa District, Gorontalo Regency, affected by floods is Balahu Village. The flood problem in Balahu Village is a serious issue and requires solutions to minimize the negative impacts caused by the periodic floods that occur every year. To address this problem, the Thematic KKN Program was implemented by developing and applying innovations to face disaster threats, through the mapping of natural disaster evacuation routes and disaster mitigation training for the Balahu Village community. The method used in this Thematic KKN Program to create evacuation route maps utilized network analysis. Students and the community collaborated in mapping evacuation routes, creating direction signs, and conducting disaster evacuation simulations with the support of relevant agencies, resulting in evacuation route maps ready for use during disasters. The UNG Thematic KKN 2024 activities provided significant benefits by contributing to the development of geophysical knowledge in disaster management, providing information on flood evacuation route mapping, enhancing community understanding of disaster mitigation, and strengthening community self-reliance and resilience in facing natural disasters.